2019
DOI: 10.1186/s12859-019-3041-9
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the regulation of miRNAs on protein-protein interaction network in Hodgkin lymphoma

Abstract: Background Hodgkin Lymphoma (HL) is a type of aggressive malignancy in lymphoma that has high incidence in young adults and elderly patients. Identification of reliable diagnostic markers and efficient therapeutic targets are especially important for the diagnosis and treatment of HL. Although many HL-related molecules have been identified, our understanding on the molecular mechanisms underlying the disease is still far from complete due to its complex and heterogeneous characteristics. In such s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…However, in reality, PPI network has dynamic property, which is intrinsically regulated by complex cellular mechanisms through time and space (Liang and Li 2007). Recent studies showed the significance of the miRNA regulation on protein-protein interaction networks (Rahimpour et al 2022;Du et al 2019;Lei et al 2019;Liang and Li 2007). Moreover, different methods have been developed to predict miRNA targets accurately at the genomic level (John et al 2004;Lewis et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, in reality, PPI network has dynamic property, which is intrinsically regulated by complex cellular mechanisms through time and space (Liang and Li 2007). Recent studies showed the significance of the miRNA regulation on protein-protein interaction networks (Rahimpour et al 2022;Du et al 2019;Lei et al 2019;Liang and Li 2007). Moreover, different methods have been developed to predict miRNA targets accurately at the genomic level (John et al 2004;Lewis et al 2003).…”
Section: Introductionmentioning
confidence: 99%